Analysis on Cracking Failure of Ball Mill Speed Transmission - MENG Hua, WANG Qian (Cailiao Baohu, 2021)
The bevel gear of transmission of ball mill in a mine cracked affer 10 d of use, for this, the chemical composition, mechanical properties, microstructure and fracture morphology of ball mill gears were studied by means of direct reading spectrometer, tensile tester, Vickers hardness tester, metallographic microscope and SEM. Results showed that the metallographic, hardness and composition of the gear met the technical requirements. The crack source of the fracture was located in the inside of the fracture, and there were many O, Al, Ca, Na and other non-metallic inclusions in the crack source. These inclusions had high hardness, cut the material matrix, which made the matrix produce the hole effect and stress concentration when subjected to the external force. According to the fracture mechanics calculation, the stress concentration caused by inclusions was about 200 MPa, which was superposed with the residual stress after quenching. This was the main cause of tooth cracking for the gear. The improvement measure adopted was to change the raw material supply from ordinary steel plant to special steel plant, so as to reduce the content of inclusions in the steel. It was proved by practice that the cracking problem of gear was completely solved by the improvement measures.